2016
DOI: 10.1080/09540121.2016.1146401
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence among transgender women living with HIV

Abstract: Medication adherence is linked to health outcomes among adults with HIV infection. Transgender women living with HIV (TWLWH) in the U.S. report suboptimal adherence to medications and are found to have difficulty integrating HIV medication into their daily routine, but few studies explore factors associated with medication adherence among transgender women. Thus, the purpose of this paper is to examine demographic and clinical factors related to self-reported medication adherence among transgender women. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 10 publications
4
41
2
Order By: Relevance
“…The levels of engagement in care and viral suppression reported in this sample of TF youth is similar to that of TF adults sampled in San Francisco [29], yet suboptimal relative UNAIDS 90-90-90 targets [75]. Consistent with research conducted in TG adults [28, 42, 76], medication adherence and retention in care were also suboptimal as only 55.0% of those currently taking medications had been adherent in the past 7 days and 33.9% had missed one or more HIV care appointment in the past 6 months. Additionally, in multivariable models, medical gender affirmation was associated with reduced odds of virological suppression and with increased odds of missing appointments.…”
Section: Discussionsupporting
confidence: 70%
“…The levels of engagement in care and viral suppression reported in this sample of TF youth is similar to that of TF adults sampled in San Francisco [29], yet suboptimal relative UNAIDS 90-90-90 targets [75]. Consistent with research conducted in TG adults [28, 42, 76], medication adherence and retention in care were also suboptimal as only 55.0% of those currently taking medications had been adherent in the past 7 days and 33.9% had missed one or more HIV care appointment in the past 6 months. Additionally, in multivariable models, medical gender affirmation was associated with reduced odds of virological suppression and with increased odds of missing appointments.…”
Section: Discussionsupporting
confidence: 70%
“…also showed disparities with ART at one clinical site, with fewer TGW (59%) than non-transgender people (82%) taking ART [24]. Even when receiving ART, TGW have been shown to be significantly less likely to report optimal adherence [25]. A study examining community viral load in San Francisco demonstrated that TGW had a higher community viral load, almost three times compared to non-transgender persons, consistent with low rates of ART [26].…”
Section: Introductionmentioning
confidence: 99%
“…A recent substudy of the iPrEx trial revealed that TGW were less likely to have detectable drug levels compared to non-transgender MSM [30]. Furthermore, TGW may have concerns about potential interactions between feminizing hormone regimens and PrEP that reduce the likelihood of PrEP uptake among HIV-negative TGW [25]. …”
Section: Introductionmentioning
confidence: 99%
“…A few smaller community samples (N = 22 to N = 181) report lower ART adherence rates spanning from 55% to 68% among predominantly transgender women samples, although measurement of adherence varies across studies. 12,[16][17][18][19][20] Community studies of transgender populations report adherence barriers such as negative health care experiences 16 and transphobia. 12 The National HIV/AIDS Strategy for the United States calls for improving health outcomes and decreasing health disparities among transgender people.…”
Section: Introductionmentioning
confidence: 99%
“…12 The National HIV/AIDS Strategy for the United States calls for improving health outcomes and decreasing health disparities among transgender people. 21 Meeting these goals necessitates better understanding of HIV adherence among this population, 18 although existing national community samples are few. 12 In this study we use the U.S. Transgender Survey (USTS) to explore factors associated with ART adherence among TGNC PLWH based on both the adherence literature and availability of variables in the USTS, including 22 demographics, health and health care indicators, substance use, and recent negative experiences of discrimination and sexual assault.…”
Section: Introductionmentioning
confidence: 99%